FRI0298 Differences Between Clinical and Densitometric Risk Factors in Patients with and Without Fragility Fractures in a Bone Metabolism Unit (BMU). (9th June 2015) - Aznar, J.J.; Rojas, S.M.; Mellado, L.M.; Cossío, P.J.; Rodriguez Araya, T.L.; Veroz, R.; Gallego, A.M.; Chamizo, E.
Abstract : Background: Identification of fracture risk factors, Bone Mineral Densitometry (BMD) and FRAX application have helped to decrease the variability of the diagnosis and treatment in patients with osteoporosis (OP). More investigation is needed to identify the differences between patients that are susceptible to fractures. Objectives: Identify the differences in BMD and fracture risk factors (FRAX) between patients with and without fragility fractures. Methods: Patients attended a high resolution consultation of OP in the BMU of the Rheumatology Unit in the Hospital of Mérida, from July 2013 to June 2014, collecting information about fracture risk factors, lumbar-BMD (L2-L4) and hip-BMD, radiology of dorsolumbar spine and vitamin D. FRAX with and without BMD was calculated in all patients. Results: We studied 355 patients who had all the information needed. 81 patients presented clinical or morphometric fractures, with a mean age of 69.28±2, 88 years, slightly higher than the 274 patients without fractures (62.61±1.31). The differences in the rates of densitometric OP between fractured and non-fractured patients were 23.4% and 21.1% in lumbar spine and 18.5% and 10.9% in hip with an OR 1.85 (0.94-3.64) and Ji 2 3.24 (p=0.07). The rate of fractured patients with Major osteoporotic fracture >10% and hip fracture >3% in FRAX were 12.34% and 22.22%. When DMO is added to the calculation the rates increased to 16.04% and 23.45%, respectively. In non-fractured patients, the rate of major fracture of 20.43% and hip fracture of 25.18% decreased when DMO was added to the calculation of FRAX to 14.96% and 21.89%, respectively. The rate of patients with levels of vitamin D<20ng/ml was 19.75% in fractured patients and 16.05% in non-fractured patients. Conclusions: The Mean age in fractured patients was higher than in non-fractured patients, in accordance to other studies in the literature that age is an important risk factor for fractures. The rate of desitometric OP in patients with or without fractures was similar in lumbar spine, but we find higher rate of hip OP in fractured patients although without statistical differences. In our study, the calculation of FRAX without BMD underestimates the fracture risk in fractured patients respect to the non-fractured patients. However, when the BDM is added to the calculation of FRAX, this evaluation of the fracture risk in fractured patients improves. We didn't find any statistically difference between rates of patients with levels of vitamin D<20ng/ml and >20ng/ml. Disclosure of Interest: None declared